Tibetan medicine salidroside improves host anti-mycobacterial response by boosting inflammatory cytokine production in zebrafish - He, Shumei; Fan, Hongyan; Sun, Bin; Yang, Meipan; Liu, Hongxu; Yang, Jianwei; Liu, Jianxin; Luo, Sizhu; Chen, Zihan; Zhou, Jing; Xia, Lu; Zhang, Shulin; et al. (Frontiers in Pharmacology, 2022)
Treatment of Tuberculosis (TB), especially multidrug-resistant TB (MDR-TB), has a prolonged cycle which can last up to a year. This is partially due to lack of effective therapies. The development of novel anti-TB drugs from the perspective of host immune regulation can provide an important supplement for conventional treatment strategies. Salidroside (SAL), a bioactive component from the Tibetan medicine Rhodiola rosea, has been used in the treatment of TB although its mechanism remains unclear. Here, a bacteriostatic effect of SAL in vivo was first demonstrated using zebrafish – M. marinum infection model. To further investigate the underlying mechanism, we then examined the impact of SAL on immune cell recruitment during wound and infection. Increased macrophage and neutrophil infiltrations were found both in the vicinity of the wound and infection site after SAL treatment compared with control, which might due to the elevated chemokine expression levels after SAL treatment. SAL treatment alone was also demonstrated can improve the survival of infected zebrafish larvae, an effect that was amplified when combining SAL treatment with isoniazid or rifampicin. Interestingly, the reduced bacterial burden and improved survival rate under SAL treatment were compromised in tnfα deficient embryos, which suggests a requirement of Tnfα signaling on the anti-mycobacterial effects of SAL. To summary, this study not only provide the cellular and molecular mechanisms for the host anti-mycobacterial effects of the Tibetan medicine SAL, but also provides proof of concept that combined application of SAL with traditional anti-TB drugs could be a novel strategy to improve treatment efficacy.